The Influence Of Brand Image And Word Of Mouth (WOM) On Interest In Saving At Indonesian Sharia Banks (Case Study: Students of the Faculty of Islamic Economics and Business, UIN Sulthan Thaha Saifuddin Jambi) - Jose Arwando; Elyanti Rosmanidar; Dessy Anggraini (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This research endeavor seeks to examine the impact of brand image and word of mouth (WOM) on the propensity to save at Bank Syariah Indonesia, focusing specifically on the student population within the Faculty of Islamic Economics and Business at Sulthan Thaha Saifuddin Jambi State Islamic University. The methodology employed in this investigation is a quantitative approach, with data acquisition facilitated through the administration of questionnaires distributed to the selected respondents. The analytical technique utilized for data interpretation in this study is multiple linear regression, utilizing the SPSS software for computational assistance. The findings of this research indicate that, in isolation, brand image exerts a positive and statistically significant effect on the inclination to save. Likewise, word of mouth (WOM) demonstrates a positive and significant influence on saving interest. Collectively, brand image and word of mouth (WOM) exert a notable effect on the saving interest of students at Bank Syariah Indonesia.